The Lengyel Culture in Croatia - Težak-Gregl, Tihomila (1999)
The article discusses the phenomenom of the Lengyel Culture in northern part of inland Croatia mostly based on the recent results of the archaeological excavations of prehistoric settlement Ozalj - Stari Grad.
Projekt MZOS
ENG